2014
DOI: 10.1159/000367716
|View full text |Cite
|
Sign up to set email alerts
|

Combined 23-Gauge Vitrectomy and Femtosecond Laser-Assisted Cataract Surgery

Abstract: Background: The aim of this study was to assess the safety and surgical results of femtosecond laser-assisted phacovitrectomy. Methods: A retrospective analysis of the medical records of patients over 50 years of age with vitreoretinal pathology, who had undergone pars plana vitrectomy using 23-gauge instruments and femtosecond laser-assisted cataract surgery and implantation of an intraocular lens, was performed at the Instituto de Microcirugía Ocular between June 2012 and September 2013. The diameter of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…FLACS was started in 2009 with incorporation into routine surgical practice occurring in 2010 [4,14]. e efficacy and safety of FLACS with 23gauge and 25-gauge vitrectomy have been published [5,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FLACS was started in 2009 with incorporation into routine surgical practice occurring in 2010 [4,14]. e efficacy and safety of FLACS with 23gauge and 25-gauge vitrectomy have been published [5,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Gomez-Resa et al published a study including 21 eyes of 21 patients who underwent 23-gauge pars plana vitrectomy and femtosecond laser-assisted cataract surgery. e diameter of the capsulorhexis was chosen as 4.8 mm in eyes where the use of a gas tamponade was expected (e.g., macular hole) and 5 mm in all other eyes, and they reported that all the IOLs remained well positioned at 3 months follow-up [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent technique using a femtosecond laser in cataract surgery requires the operating room to be kept at approximately 20°C with low humidity to maintain the performance of the femtosecond laser 18 19. The combination of femtosecond laser-assisted cataract surgery and vitrectomy has been reported to enhance the accuracy of the surgery 20 21.…”
Section: Discussionmentioning
confidence: 99%
“…have used a scleral buckle in the single case that was found to have a retinal detachment intraoperatively in spite of doing 23-gauge vitrectomy with a femto cataract surgery. [4]…”
mentioning
confidence: 99%